Pyelonephritis and Bacteremia from Lactobacillus delbrueckii - DuPrey, Kevin M. (Hindawi Publishing Corporation, 2012)

(untitled)
Lactobacilli are normal colonizers of the oropharynx, gastrointestinal tract, and vagina. Infection is rare, but has been reported in individuals with predisposing conditions. Here we describe the case of a woman with pyelonephritis and bacteremia in which Lactobacillus delbrueckii was determined to be the causative agent.